Evaluation of the Implementation of the Merdeka Belajar Kampus Merdeka Policy at a Private University in South Tangerang - PURWANTO, Dr. Edi; CITRANINGTYAS, Clara Evi C. (CENTRAL ASIA AND THE CAUCASUS, 2021)
The purpose of this study is to measure student interest and satisfaction in participating in the Independent Learning-Independent Campus program established by the Indonesian Ministry of Education and Culture, Research and Technology, to identify obstacles to implementing the program, and to find corrective actions for implementation that was not optimal. This research used a mix-method based on survey data on 1,638 students and focused on group discussions (FGD) interviews. The results showed that most of the students were interested in joining the Independent Learning-Independent Campus program, but others still showed low interest. This was because the information and procedures related to the newly launched program were still unclear. Increasing the intensity of socialization, utilizing the role of lecturers to convey information, and encouraging students to participate in the program are expected to boost their interest.